Pattern of consumption of psychoactive substances in alternative transport drivers. - Branco,Fernanda (2020)
Abstract Introduction: The alternative transport drivers, more commonly known as "pirateiros” are constantly exposed to various health-threatening situations, such as the consumption of psychoactive substances. Objectives: To identify patterns of consumption of psychoactive substances in alternative transport drivers. Methods: A descriptive study with a quantitative approach, performed with a sample of 40 “pirateiros” drivers in the city of Oiapoque, in the state of Amapá, Brazil. There was use of a sociodemographic questionnaire, and the Alcohol, Smoking and Substance Test (ASSIST). The data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 22.0. Results: The “pirateiros” drivers consumed psychoactive substances: 87.5% used tobacco derivatives, alcohol 100%, 37.5% marijuana, 15% cocaine and crack, 65% amphetamine and 2.5% inhalants and deny the use of hypnotics, sedatives, hallucinogens and opiates. Through the questionnaire ASSIST on consumption patterns, 62.5% occasionally used marijuana and 86.4% and 67.6% resorted to the abusive use of amphetamines and tobacco derivatives, respectively. In relation to the consumption of alcoholic beverages, 28.2% showed indicative of dependency. Conclusions: The results show the need for more specific investigations, and the reflection on the situation of vulnerability of “pirateiros” strongly raised in this study. The research reveals the need to entice professionals to develop concrete actions for health education for this professional category.